Effect of walking and summer stress on physiological, heamatological and antioxidant profiles in mithun bulls - PERUMAL, P; KHAN, M H; CHANG, SUKKUM; SANGMA, C T R (The Indian Journal of Animal Sciences, 2016)
The study was conducted to evaluate effect of walking stress on physiological, heamatological and antioxidant profiles in mithun bulls. Mithun bulls (12) of adult age of 4 to 6 yr (500–600 kg body weight) with body condition score 5–6 were selected and divided into group 1 (6): control (not exposed to walking and thermal stress) and group 2 (6): treatment (exposed to walking and thermal stress). The treatment group was allowed to walk 15 km to and fro from the farm without allowing grazing. The control animals were kept in the adjacent shed covered with asbestos sheets and surrounded by big trees. The time of walking was from 0900 h to 1400 h. The experiment was conducted during summer (May to July). Immediately after stress, the animals were restrained and physiological parameters such as rectal temperature (RT), respiration rate (RR), pulse rate (PR), heart rate (HR), skin temperature (ST) were measured. Meanwhile, blood samples were collected to study the heamatological such as red blood cells (RBC), haemoglobin (Hb), erythrocyte sedimentation rate (ESR), packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC) and antioxidant profiles such as reduced glutathione (GSH), glutathione reductase (GSHRx), superoxide dismutase (SOD), catalase (CAT), total antioxidant capacity (TAC) and lipid peroxide such as malondialdehyde (MDA). The result revealed that physiological, heamatological profiles and MDA were significantly higher and antioxidant profiles were significantly lowered in stressed animals than in unstressed animal group. It was concluded that the walking stress and hot summer stress has significantly affected the performance of mithun.